2005
DOI: 10.1111/j.1747-0765.2005.tb00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-term Fertilizer Application on the Concentration and Solubility of Major and Trace Elements in a Cultivated Andisol

Abstract: The concentrations and solubility of major and trace elements in soils collected from a field for long‐term experiments maintained for more than 60 years and the neighboring area were investigated in order to reveal the influence of soil management on their behavior in soils. No obvious differences in the element concentrations in soils were observed except for P and U, whose concentrations were elevated in the surface soils of the experimented field because of the long‐term application of phosphate fertilizer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…By contrast, low pH in the soil, caused by more than 60 years of rice straw compost applications, may have enhanced the concentration of metals in the water-soluble fraction (Takeda et al, 2005).…”
Section: Heavy Metal Concentration In the Agro-ecosystemmentioning
confidence: 98%
“…By contrast, low pH in the soil, caused by more than 60 years of rice straw compost applications, may have enhanced the concentration of metals in the water-soluble fraction (Takeda et al, 2005).…”
Section: Heavy Metal Concentration In the Agro-ecosystemmentioning
confidence: 98%
“…Thus, the main objective of the present study was to examine the detailed effect of acidification on the allophanic Andisol using the selective dissolution analysis. When the WS fraction increases, the WS elements may translocate downward in a humid climate although TCE in the Ap horizon soil was only slightly affected by the present degree of acidification (Takeda et al 2005). However, the allophanic Andisol in this area was derived from several tephra deposits of different ages from the Towada caldera (Shoji, Nanzyo, and Dahlgren 1993).…”
Section: Introductionmentioning
confidence: 97%
“…A long-term experimental field, established in 1940 at the Fujisaka Branch, Aomori Agricultural Experiment Station in Towada, Aomori Prefecture, Japan (latitude: 409 35u N, longetude: 1419 15u E), was used to examine the effect of fertilizer application on the chemical composition of an allophanic Andisol. We previously found that the solubility of lithium (Li), beryllium (Be), Al, manganese (Mn), cobalt (Co), zinc (Zn), yttrium (Y), cadmium (Cd), barium (Ba), and rare-earth elements in soil increased, whereas the solubility of phosphorus (P), arsenic (As), selenium (Se), niobium (Nb), antimony (Sb), molybdenum (Mo), and vanadium (V) decreased with acidification (Takeda et al 2005). However, the total concentration of the studied elements were only slightly affected by the long-term fertilizer application except for P and uranium (U) (Takeda et al 2005).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Several long-term fertilizer experiments have been conducted to quantify changes in major and trace elements in soils [2]. Phosphorus (P) deficiency is a universal constraint to crop production and constitutes the second most important soil fertility problem throughout the world [3].…”
Section: Introductionmentioning
confidence: 99%